Patofyziologické mechanizmy predsienových porúch rytmu. II. Predsienový flutter - Stancák, B (Vnitrni lekarstvi, 1998)
Atrial flutter is a common cardiac dysrhythmia which responds for half of the supraventricular tachycardias with exception of atrial fibrillation. Activation and entrainment mapping studies in man and in animals confirmed the reentry mechanism of atrial flutter and demonstrated that the reentry circuit is located in the right atrium. The most important anatomical structures which enable the occurrence of atrial flutter are crista terminalis, Eustachian valve/ridge and tricuspid annulus. In typical atrial flutter the impulse rotates "counterclockwise". According to the present knowledge the reentry circuit surrounds a central obstacle made by the orifices of the superior and inferior vena cava linked by a line of functional block in the region of crista terminalis. The anterior barrier is created by tricuspid annulus. The anterolateral wall of the right atrium is activated craniocaudally. Crista terminalis and tricuspid annulus form a funnel which leads the impulse into the isthmus with slow conduction located between the vena cava orifice and tricuspid annulus. Septal activation is ascending and the activation wave considerably widens and becomes irregular. The upper link of the circuit is located above and anteriorly to the superior vena cava. The left atrium is activated passively and does not play an important role in the reentrant circuit. Reverse flutter has the same substrate as typical flutter but rotates in an opposite "clockwise" manner.
Keywords: flutter síní; Atrial Flutter; převodní systém srdeční; Electrophysiology; elektrofyziologie; zvířata; Humans; Heart Conduction System; lidé; Animals